Role of serum (1,3)‐β‐d‐glucan assay in early diagnosis of invasive fungal infections in a neonatal intensive care unit - Abd Elazeez Shabaan; Lobna Mahmoud Elbaz; Wafaa M. El‐Emshaty; Basma Shouman (Brazilian Society of Pediatrics, 2018)
Objectives: To study the microbiological pattern of late onset neonatal sepsis cultures and to assess the diagnostic performance of serum (1,3)‐β‐d‐glucan level for early diagnosis of invasive fungemia in high‐risk infants admitted to a neonatal intensive care unit. Methods: A prospective multicenter clinical trial conducted on infants at high risk for invasive fungal infections, with suspected late onset sepsis, admitted to a neonatal intensive care unit at Mansoura University Children's Hospital and Mansoura General Hospital between March 2014 and February 2016. Results: A total of 77 newborn infants with high risk of invasive fungal infection were classified based on blood culture into three groups: no fungemia (41 neonates with proven bacterial sepsis), suspected fungemia (25 neonates with negative blood culture), and definite fungemia group (11 neonates with culture‐proven Candida). The growing organisms were Klebsiella spp. (14/54); Escherichia coli (12/54); Staphylococcus spp. (12/54; coagulase‐negative Staphylococcus [9/54]; Staphylococcus aureus [3/54]); Pseudomonas aerouginosa (3/54); and Proteus spp. (2/54). Moreover, 11/54 presented Candida. Serum (1,3)‐β‐d‐glucan concentration was significantly lower in the no fungemia group when compared with the definite fungemia group. The best cut‐off value of (1,3)‐β‐d‐glucan was 99 pg/mL with sensitivity, specificity, positive predictive value, negative predictive value, and accuracy of 63.6%, 95.1%, 77.8%, 90.7%, and 88.5%, respectively. Conclusion: (1,3)‐β‐d‐glucan assay has a limited sensitivity with excellent specificity and negative predictive value, which allow its use as an aid in exclusion of invasive neonatal fungal infection. Accurate diagnosis and therapeutic decisions should be based on combining (1,3)‐β‐d‐glucan assay with other clinical, radiological, and microbiological findings. Resumo: Objetivos: Estudar o padrão microbiológico das culturas de sepse neonatal de início tardio e avaliar o desempenho diagnóstico do nível de (1,3)‐β‐D‐glucano no soro para diagnóstico precoce de fungemia invasiva em neonatos de alto risco internados em uma unidade de terapia intensiva neonatal. Métodos: Ensaio clínico multicêntrico prospectivo conduzido em neonatos internados em uma unidade de terapia intensiva neonatal com suspeita de sepse de início tardio que estavam em risco de infecções fúngicas invasivas no hospital universitário infantil de Almançora e no hospital geral de Almançora entre março de 2014 e fevereiro de 2016. Resultados: Foram classificados 77 neonatos recém‐nascidos com risco de infecção fúngica invasiva, com base na hemocultura, em: grupo sem fungemia, incluindo 41 neonatos com sepse bacteriana comprovada, grupo com suspeita de fungemia, incluindo 25 neonatos com hemocultura negativa; e grupo com fungemia definida, incluiu 11 neonatos com Candida comprovada por cultura. Os organismos em crescimento foram: {Klebsiella spp 14/54; E. coli 12/54; Staphylococcus spp 12/54 (Staph coagulase negativa 9/54; Staph aureus 3/54); pseudomonous aerouginosa 3/54 e Proteus spp 2/54}, além de 11/54 Candida. A concentração de (1,3)‐β‐D‐glucano no soro foi significativamente inferior no grupo sem fungemia em comparação ao grupo com fungemia definida. O melhor valor de corte da (1,3)‐β‐D‐glucano foi 99 pg/mL com sensibilidade, especificidade, valor preditivo positivo, valor preditivo negativo e precisão de 63,6%, 95,1%, 77,8%, 90,7% e 88,5%, respectivamente. Conclusão: O ensaio de (1,3)‐β‐D‐glucano possui sensibilidade limitada com especificidade e valor preditivo negativo excelentes que possibilitam seu uso e ajudam na exclusão de infecção fúngica invasiva neonatal. O diagnóstico preciso e as decisões terapêuticas devem ter como base a combinação de ensaio de (1,3)‐β‐D‐glucano com outros achados clínicos, radiológicos e microbiológicos. Keywords: (1,3)‐β‐d‐glucan, Invasive candidiasis, Neonatal sepsis, Palavras‐chave: (1,3)‐β‐D‐glucano, Candidíase invasiva, Sepse neonatal